Inflows of Capital to Developing Countries in the 1990s: Causes and Effects - Leonardo Leiderman; Guillermo A. Calvo; Carmen Reinhart (Inter-American Development Bank, Office of the Chief Economist, 1994)
This paper discusses the changing pattern of capital flows to developing countries. The analysis is heavily colored by recent events. It concentrates on the principal facts, developments, and policies that characterize the current episode of capital inflows to Asia and Latin America.
Keywords: 330